Superior sodium storage of novel VO2 nano-microspheres encapsulated into crumpled reduced graphene oxide. Issue 10 (15th February 2017) - Yan, Bo; Li, Xifei; Bai, Zhimin; Lin, Liangxu; Chen, Gang; Song, Xiaosheng; Xiong, Dongbin; Li, Dejun; Sun, Xueliang
Abstract : A crumpled rGO encapsulated VO2 anode fabricated by using a scalable reaction system exhibits outstanding rate capacities and cycling stabilities for sodium storage. Abstract : To uniformly encapsulate electrode materials with reduced graphene oxide (rGO) has been a considerable challenge due to the lack of appropriate synthetic methods and/or effective reaction systems. In this study, we present a one-step rapid and scalable solvothermal approach to achieve a crumpled reduced graphene oxide encapsulated VO2 material. As a demonstration of this promising configuration, for the first time, we systematically studied its Na + storage behavior in the voltage range of 3.0 to 0.01 V ( versus Na/Na + ). It turned out that the as-prepared anode material exhibits high reversible capacities of 383 mA h g −1 at 0.1 A g −1 and 214 mA h g −1 at 4 A g −1, and can stably operate for as long as 2000 cycles at 4 A g −1 with a capacity fade of 0.013% per cycle, resulting from the improved electronic conductivity, structural stability, and electrode wettability. Furthermore, the formation mechanism and structural features of the desired crumpled reduced graphene oxide encapsulated VO2 material are discreetly expounded. More interestingly, a chain of cogent evidence is provided by coating on various electrode materials to confirm the scalability of this facile and rapid solvothermal synthesis method, which would open up a novel avenue to create more fascinating graphene-based functional materials for the multitudinous application domain.